ANALISA PROSEDUR PEMBELIAN BARANG DI BAGIAN PURCHASING PADA PT. PYLAR SURYA INDONESIA - Wulandari, Aisyah; Takaya, Rowlan (Jurnal Pijar, 2024)
Purchasing is an effort made by a company to obtain the products it needs. Inventory of raw materials is the most important factor for companies in supporting the smooth production process. The method used in this journal research is observational. This means that we make direct observations of goods purchasing activities in the purchasing section at PT. Pylar Surya Indonesia. Next we asked several questions to interview buyers at PT. Pylar Surya Indonesia has questions regarding the contents of this Journal. Next, use the library study method to look for book references related to fields related to the research subject. The results of this research are the process of purchasing goods at PT. Pylar Surya Indonesia is running smoothly, but there are problems such as the product received is different from the order. However, this problem will be resolved by returning the goods to the supplier and exchanging them according to the order issued.